Die Odonaten der Sammelreise R. Petrovitz und F. Ressl aus Kleinasien. - Quentin, Douglas St. (Contributions to Entomology = Beiträge zur Entomologie, 1964)
The publication deals with the Odonata, 22 species, of two collecting trips from Asia Minor; Platycnemis pennipes kervillei (Martin), the female of Onychogomphus assimilis (Schneider), the distinguishing characters of Anaciaeschna isosceles isosceles (Müller) and isosceles humeralis Schmidt are described and figured; the form of Orthetrum sabina (Drury) from Asia Minor is seperated as subspecies under the name O. sabina ampullacea (Schneider).